Effect of Reperfusion on Time Domain Parameters of Heart Rate Variability - Sadia Mubarak; Bushra Riaz; Mehvish Ashfaq; Sidra Hamid; Amina Rasul; Mamoona Shafiq (Journal of Rawalpindi Medical College)
Objective: To compare effect of reperfusion by measuring time domain parameters of heart rate variability before and after percutaneous transluminal coronary angioplasty. Study design: Quasi experimental study design Place and Duration: Department of Clinical Cardiac Electrophysiology, Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi from January 2014 till January 2015. Patients and Methods: 40 patients with coronary artery disease having mean age of 55.20 ± 8.03 years were recruited by non-probability convenience sampling. DMS 300-4A Holter monitors were used to obtain 24 hours ambulatory ECG recording before and within 24 hours after percutaneous transluminal coronary angioplasty. Digital ECG data were transferred to the computer and edited with the help of DMS Cardioscan software. Heart rate variability was analysed in time domains measures. For time domain analysis normal heart rate, SDNN, SDNNi, SDANN, RMSSD and pNN50 were recorded from 12 lead digital ECG data.